2016
DOI: 10.21608/bvmj.2016.31301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of Pseudomonas species in frozen imported meat

Abstract: A total of 90 random samples of Frozen American, Brazilian and Indian meat samples (30 of each) were collected from different retail shops and supermarkets in EL-Menofeya Governorate at different production dates. The collected samples were examined bacteriologically and by using PCR tecnique for detection of Pseudomonas species, especially

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…in chicken: P. libanensis , P. extremorientalis , P. antarctica , P. veronii , P. synxantha , P. marginalis , P. cedrina , P. koreensis , P. brenneri , and P. trivialis . The presence of P. orientalis has also been found in meat by other authors [ 50 ]. We also isolated other Pseudomonas spp., including P. rhodesiae , P. azotoformans , and P. kilorensis .…”
Section: Discussionsupporting
confidence: 61%
“…in chicken: P. libanensis , P. extremorientalis , P. antarctica , P. veronii , P. synxantha , P. marginalis , P. cedrina , P. koreensis , P. brenneri , and P. trivialis . The presence of P. orientalis has also been found in meat by other authors [ 50 ]. We also isolated other Pseudomonas spp., including P. rhodesiae , P. azotoformans , and P. kilorensis .…”
Section: Discussionsupporting
confidence: 61%
“…( 2016 ) reported that 97.90% of beef samples were positive for P. aeruginosa strains. Other surveys were conducted on chicken meat (Mahato et al., 2020 ), camel meat (Osman et al., 2019 ), cattle meat (Odoi et al., 2021 ), frozen meat (Ibrahim et al., 2016 ) and meat products (Sofy et al., 2017 ) samples showed that the P. aeruginosa prevalence had a range between 3.00 to 80.00%. High adaptation of P. aeruginosa strain in different temperatures (4–42°C) and water activities (72–97%) (Gu et al., 2016 ) may be another reason for its high prevalence among the examined samples.…”
Section: Discussionmentioning
confidence: 99%
“…fluorescence in imported frozen meat was 64.44%, 46.67% and 73.33%, respectively. Abd Elaal (2017) and Ibrahim et al (2016) those reported that the incidence of Ps. putida in imported frozen meat was (8.34%) and (8.34%) respectively.…”
Section: Disucssionmentioning
confidence: 97%
“…The incidence of Pseudomonas species isolated from the examined samples was 70%, 80% in frozen cubic meat and minced meat, respectively. Ibrahim, et al, (2016) those explained that the incidence of Ps. fluorescence in imported frozen meat was 64.44%, 46.67% and 73.33%, respectively.…”
Section: Disucssionmentioning
confidence: 99%